A STUDY THE NEEDS OF USING THAI LANGUAGE IN BUSINESS FOR CHINESE STUDENTS AT YUNNAN UNIVERSITY OF FINANCE AND ECONOMICS OF CHINA - Ziyu, Fang; Suthasinobol, Kittichai; Satjapiboon, Suppawan; Langka, Wilailak (Journal of Buddhist Anthropology, 2021)
The Objectives of this research article were to 1) Study the needs of using Thai language in business for Chinese students at Yunnan University of Economics and Finance, China 2) Explore ways to empower Chinese students in Yunnan University of Economics and Finance in China with capacity and competence of learning to enhance Thai language proficiency especially in business. The sample group used in the research are consist of 3 graduate employers, 5 Chinese graduates in Thai language program, 3 Thai language in business teaching specialist, and 103 Chinese students in Thai language program. There are two types of research instruments including structural interview and rating scale questionnaire are adopted in this research. Data collection is divided into 2 phases: Phase I, data have been collected through in-depth interviews, and Phase II, collecting data by using questionnaires distributed to the Chinese students in Thai language program. The statistics used for data analysis are mean and standard deviation The results of the research suggest that: In Chinese business, there is a need for Chinese students in Thai language program from Yunnan University of Economics and Finance, have the ability to use Thai language in 7 business contexts including workplace, service, business seminar, business travel, trade, investment, and hospitality contexts. Results of data analysis suggest that Chinese students in Thai language program need to use Thai language in business at the high level ( = 4.23, S.D.=0.85). Analysis of guidelines for teaching development of Thai language in business courses for Chinese students can be divided into 3 ways including curriculum development, development of teaching and learning activities, and development of teaching materials.